A panorama of the role of classical quality tools in Industry 4.0 through bibliometric indicators - Adigneri, Helton Messias; Santos, João Manoel da Silva dos; Galdamez, Edwin Vladimir Cardoza; Santos, Bruno Samways dos (Brazilian Journal of Production Engineering, 2026)
With the transition to Quality Management 4.0, questions arise regarding the role played by classical quality tools, which have been used since the twentieth century. To investigate this issue, a bibliometric analysis study was conducted using articles published in the Web of Science database that presented applications of classical quality tools in conjunction with the pillars of Industry 4.0. With the support of the VOSviewer software, bibliometric indicators were generated and analyzed. The results showed that stratification, histograms, and control charts were mainly used in combination with big data, simulation, and robotics. It was concluded that, in practice, these quality tools are used by Industry 4.0 organizations in environments characterized by large data flows, gaining new applications beyond process monitoring and being employed in other non-traditional industrial applications. Thus, this study indicates that there are still research gaps to be explored to ensure the effective integration of quality tools with the technological environment, especially regarding the Pareto diagram, the cause-and-effect diagram, and the scatter diagram.